Imatinib in myeloid/lymphoid neoplasms with eosinophilia and rearrangement of PDGFRB in chronic or blast phase - Jawhar, Mohamad; Naumann, Nicole; Schwaab, Juliana; Hofmann, Wolf-Karsten; Fabarius, Alice; Reiter, Andreas; Metzgeroth, Georgia (Annals of hematology, 2017)
We evaluated clinical characteristics and outcome on imatinib of 22 patients with myeloid/lymphoid neoplasms with eosinophilia and rearrangement of PDGFRB. Median age was 49 years (range 20-80), 91% were male. Fifteen different PDGFRB fusion genes were identified. Eosinophilia was absent in 4/19 (21%) cases and only 11/19 (58%) cases had eosinophils ≥1.5×109/L. On imatinib, 17/17 (100%) patients in chronic phase achieved complete hematologic remission after median 2 months (range 0-13)​. Complete cytogenetic remission and/or complete molecular remission by RT-PCR were achieved in 12/13 (92%) and 12/14 patients (86%) after median 10 (range 3-34) and 19 months (range 7-110), respectively. In patients with blast phase (myeloid, n = 2; lymphoid, n = 3), treatment included combinations of imatinib (n = 5), intensive chemotherapy (n = 3), and/or allogeneic stem cell transplantation (n = 3). All 3 transplanted patients (complex karyotype, n = 2) experienced early relapse. Initially, patients were treated with imatinib 400 mg/day (n = 15) or 100 mg/day (n = 7), the dose was reduced from 400 mg/day to 100 mg/day during follow-up in 9 patients. After a median treatment of 71 months (range 1-135), the 5-year survival rate was 83%; 4/22 (18%) patients died (chronic phase; n = 2; blast phase, n = 2) due to progression (n = 3) or comorbidity while in remission (n = 1). Of note, 3/4 patients had a complex karyotype. In summary, the most important characteristics of myeloid/lymphoid neoplasms with rearrangement of PDGFRB include (a) male predominance, (b) frequent lack of hypereosinophilia, (c) presentation in chronic or blast phase, (d) rapid responses and long-term remission on low-dose imatinib, and (e) possible adverse prognostic impact of a complex karyotype.